Is de stad nog leefbaar ? : verloedering en vernieuwing van de Antwerpse kernstad in de jaren 1970 - Dusar, Wouter (Leuven: KU Leuven, 2010)
"Wouter Dusar Masterproef, K.U. LeuvenPromotor: Leen Van Molle"